Pengembangan Modul Interaktif Pencegahan Bullying Siswa Remaja dengan Model RnD - Hajar Mukarromah; Itsna Iftayani; Patria Jati Kusuma (Yayasan Literasi Sains Indonesia, 2025)
This study aims to develop a bullying prevention intervention module for adolescent students in junior high schools equipped with a game called